Stability analysis of rock slope under Sujiaba overpass in Chongqing City based on kinematic and numeric methods - Wu, Renjie; Li, Zheng; Zhang, Wengang; Hu, Tao; Xiao, Shilong; Xiao, Yangjun; Zhang, Sheng; Zhang, Dengsui; Ming, Chengwu (Frontiers in Earth Science, 2023)
Rock slopes have the characteristics of complex geological conditions, weak structural surface development, steep slope, and great damage. In this study, the Sujiaba overpass slope in Chongqing was selected as the evaluation object, and the main stability evaluation methods of rock slope were analyzed. Combined with the special geological conditions and geographical location of the rock slope, through a geological survey, the slope was qualitatively analyzed based on the stereographic projection method, and the slope stability safety factor was calculated by using the finite element strength reduction method. FLAC3D was used to simulate the initial stress state of the unstable rock mass, the limit state stability of the unstable rock mass before bolt support, and the stability after bolt support. The simulation results show that the stability coefficients of selected unstable rock masses W1, W2, W6, and W7 under the limit state before bolt support are, respectively, 1.22, 1.80, 5.90, and 2.10. Unstable rock masses separate from the parent rock, causing a large displacement due to their instability and downward sliding. After bolt support, stability coefficients for those four unstable rock masses are 1.60, 2.40, 8.60, and 3.20, respectively. Under the same reduction coefficient, rock masses are stable and the displacement is small. The results show that the calculation results of the initial stress state of the rock slope are consistent with the theoretical understanding and field investigation. After the implementation of bolt support, the anti-sliding stability of unstable rock is obviously improved. The research results have important scientific guiding significance and practical value for revealing the failure mechanism of rock slope and analyzing the stability of unstable rock mass.